RANCANG BANGUN LAMPU PORTABLE OTOMATIS MENGGUNAKAN RTC BERBASIS ARDUINO - Muhamad Yusuf Iqbar; Kurnia Paranita Kartika Riyanti (Antivirus : Jurnal Ilmiah Teknik Informatika, 2020)
In everyday life, lighting is one of the basic needs, both in households, offices, and large industries. Therefore, the availability of lamps is very important. However, it is necessary to have a wise attitude in the use of this energy source of lighting. In daily activities at home, for example, many residents often forget to turn off the lights in the morning, when residents travel out of town, setting the lights on and off is a problem in itself, if the lights are not turned off it will result in a waste of electrical energy, but if it is turned off then at night it will be dark for days because the householder is not there. This often happens especially to urban residents. Therefore, automation is needed in regulating the use of electrical energy in lamps. By paying attention to this condition, the writer created an idea for a portable lamp that can be set on and off automatically and for the time it can be adjusted as needed. This portable lamp uses a voltage source from a battery so it can reduce waste of electricity energy from PLN. This automatic portable lamp is equipped with an Arduino Nano which functions as a lamp control controller, a Real Time Clock (RTC) module which functions as a timer to regulate the on and off lights, and a relay that functions as an automatic switch to turn on and turn off the lights according to the time read. on the RTC. The advantages of this portable lamp are in terms of practical packaging, it can be moved and placed anywhere as needed because it does not require an electricity connection from PLN. From the results of usage testing, this lamp can be used for 2-3 days with an active duration of 8 hours, so users don't have to worry about running out of energy sources.